The Influence of Job Satisfaction, Work Motivation and Non-Physical Work Environment on Organizational Citizenship Behavior Companion of the Family Hope Program (PKH) Indragiri Hilir Regency - Sasmita, Jumiati; Amalia, Dini (CV. Rayyan Dwi Bharata, 2025)
This study aims to investigate the influence of job satisfaction, work motivation, and the non-physical work environment on Organizational Citizenship Behavior (OCB) among Pendamping Program Keluarga Harapan (PKH) in Kabupaten Indragiri Hilir. The research employs a descriptive approach with a quantitative method. The sampling technique used is saturated sampling, involving the entire population of 74 respondents. Data analysis was conducted using SPSS Statistics 26. The findings indicate that job satisfaction has a positive and significant impact on OCB, work motivation positively and significantly affects OCB, and the non-physical work environment also positively and significantly influences OCB.